ANALISIS PROPAGASI INDOOR WLAN 802.11g PADA GEDUNG DISHUBKOMINFO KABUPATEN BADUNG - Indra Prasetya, AAN. Agung; Gunantara, N.; Sudiarta, P.K. (Jurnal SPEKTRUM; Vol 4 No 2 (2017): Jurnal SPEKTRUM, 2018)
In practice the access point can not always cover the maximum range of distance due to signal wave propagation in the room, such as reflection, alteration, or scattering of signals. For the purpose of implementation optimization, this study aims to obtain characteristics of signal level quality and throughput at the Dishubkominfo Building of Badung Regency. The indoor propagation analysis of WLAN IEEE 802.11g is based on 3 models of measurement ie without barrier, wall barrier, and floor barrier. The result of the highest signal level measurement is -40 dBm, while the lowest signal level is -85 dBm. Maximum throughput measurement results 8.05 Mbps, from the maximum available bandwidth of 10 Mbps. While the coverage area based on testers using the software to adjust the floor plan on the building, almost in accordance with the calculation of signal level.